Case Report: Response to Regional Melphalan via Limb Infusion and Systemic PD1 Blockade in Recurrent Myxofibrosarcoma: A Report of 2 Cases - Bartlett, Edmund K.; D’Angelo, Sandra P.; Kelly, Ciara M.; Siegelbaum, Robert H.; Fisher, Charles; Antonescu, Cristina R.; Ariyan, Charlotte E. (Frontiers in Oncology, 2021)
Treatment options for patients with advanced sarcoma remain limited. Promising responses to checkpoint inhibition have been observed, but responses to single-agent PD-1 inhibition are rare. We report on two patients with multiply recurrent myxofibrosarcoma treated with the combination of regionally administered melphalan (via isolated limb infusion) and pembrolizumab. Both patients had recurrent disease after multiple surgical resections and radiation. Analysis of primary tumors demonstrated microsatellite stable tumors with few mutations. After combination treatment, one patient had a significant partial response of 6 months duration, the second patient had a complete response of 2 years duration. Post treatment biopsies demonstrated immune infiltration into the tumor. These promising responses in patients with multiply recurrent myxofibrosarcoma have prompted the development of an investigator-initiated clinical trial to formally study the combination of regional melphalan and pembrolizumab in a systematic fashion (NCT04332874).